Seasonality in Spain - Davidson, Iain (Zephyrvs, 2009)
Every generation believes in the originality of its contribution to science, though this may be determined by the intellectual vogues of the day. Recent years have seen developments in Archaeology which some describe as the «New Archaeology», whilst others protest that it is but the Old in new clothes. The expansion of isotopie dating techniques and of the use of the computer have focussed attention on aspects of archaeological materials beyond imagination even 20 years ago. They are now a source of information on many forms of human variability often of importance for our understanding of modern behaviour.